Feasibility and effect of supplementing a modified OTAGO intervention with multisensory balance exercises in older people who fall: a pilot randomized controlled trial. (August 2014) - Liston, Matthew B; Alushi, Ledia; Bamiou, Doris-Eva; Martin, Finbarr C; Hopper, Adrian; Pavlou, Marousa
Objective: To investigate the feasibility and comparative effect of supplementing a modified OTAGO falls rehabilitation programme with multisensory balance exercises and informed sample size calculation for a definitive trial. Design: Single-blinded randomized controlled trial with pre/postcomparisons using a per-protocol analysis. Setting: Secondary care-based falls clinic, London, UK. Subjects: Community-dwelling older people ( n = 21) experiencing ≥2 non-syncopal falls during previous 12 months. Intervention: Modified OTAGO exercise classes supplemented with supervised home-based rehabilitation consisting of multisensory balance or stretching exercises. Group classes and home sessions each occurred twice-weekly for eight weeks. Measurements: A computerised randomization was used for group allocation. A rater, blinded to intervention, performed the assessment including the Functional Gait Assessment (primary outcome), Physiological Profile Assessment, and questionnaires relating to symptoms, balance confidence, and psychological state (secondary outcomes). Results: Significant within-group improvements were noted for the Functional Gait ( p < 0.01, r = −0.63) and Physiological Profile Assessments ( p < 0.05, r = −0.63) in the OTAGO+multisensory rehabilitation group only and for balance confidence scores in the OTAGO+stretching group ( p < 0.01, r = −0.63). Between-group differences were noted for the Functional Gait ( p < 0.01, r = −0.71) and Physiological Profile ( p < 0.05, r = −0.54) assessments with the OTAGO+multisensory group showing significantly greater improvement. The drop-out rate was similar for both groups ( 30%). No serious adverse events were reported. Conclusions: Supplementing the OTAGO programme with multisensory balance exercises is feasible in older people who fall and may have a beneficial effect on falls risk as measured using the Functional Gait and Short-form Physiological Profile Assessments. An adequately powered randomized controlled trial would require 36 participants to detect an effect size of 1.35 on the Functional Gait Assessment.